Model Contract for Health Care on Trekking and Expeditions for Doctors – Recommendation of the Medical Commission of the Union Internationale des Associations d’Alpinisme (UIAA) - Küpper, Thomas; Hillebrandt, David; Milledge, Jim; Basnayt, Buddha (Health Promotion & Physical Activity, 2020)
This suggested contract document attempts to clarify the rights and obligations of the tour operator (referred to herein as “organization”, OR), the ED and the EX to avoid trouble and misunderstandings during the trip. Being an Expedition or Trekking Doctor (referred to herein as “Expedition Doctor”, ED) is more than being merely a member which advises others in case of a health problem during the trip and who may get a discount on organized trips! An ED has specific responsibilities, has to provide special skills, and must always accept responsibility for any diagnosis made, whether right or wrong. Both, the tour operator and the participants of the Expedition (referred to herein as “Expedition”, EX) have their individual and often conflicting interests to which the ED’s own mountaineering interests must also be added. However, to minimize the possible multiple risks associated with these conflicts of interest, the rights, obligations and priorisation of medical and expedition scheduling should be made clear well in advance of the expedition. The following is a model text which may be adapted to an EX’s specific demands. In this text, EX includes the organizers of the trip, the expedition’s leaders and the participants.